Nu cerceta aceste legi că ești prea prost să le-nțelegi”. Despre justificarea normei - Rizoiu, Radu (Forum juridic)
The paper looks in to the recent practices of the Government to release new regulations limiting the individual freedom due to pandemic situation without a proper justification of the need of such harsh measures. Rather than being a paternalistic approach, the practice suggested that the Government is itself unable to explain why it took such action being believed that it preferred to copy/paste the restrictions enacted in other European countries. The thesis proposed by the paper is that (especially in these emotional periods) the Government is required to explain to the public the reason behind the rules it adopts.